Tugas Guru Dalam Perspektif Al-Qur'an - Abudullah Abudullah (Al-Riwayah : Jurnal Kependidikan, 2016)
Education is an effort to affect what is done by adult generations to those who are not ready for social life. The goal is to develop the children physically, intellectually and morally that is required by both the political society as a whole and specific environment. A teacher in education is can not separated due to several factors: first, the teacher is a man who works in an official capacity for the purpose of guiding and directing the learning experience of students in educational institutions either public or private. Second, people have a lot of experience that contribute to the growth and development of students. Third, people who have passed from professional curriculum in teacher education and training institutions which have been officially recognized by an award of appropriate teaching certificate. So, this paper will discuss the role and function of teachers in Quran.